Zero Algorithms for Avoiding Crosstalk in Optical Multistage Interconnection Network - Ali Al-Shabi, Mohammed Abdulhameed (2005)
Multistage Interconnection Networks (MINs) are popular in switching and communication applications. It had been used in telecommunication and parallel computing systems for many years. The broadband switching networks are built from 2 x 2 electro-optical switches such as Lithium Niobate switches. Each switch has two active inputs and outputs. Optical signals, carried on either inputs are coupled to either outputs by applying an appropriate voltage to the switch. One of the problems associated with these electro-optical switches is the crosstalk problem, which is caused by undesired coupling between signals carried in two waveguides. This thesis propose an efficient solution to avoid crosstalk, which is routing of traffic through an N x N optical network to avoid coupling two signals within each switching element. Under the constraint of avoiding crosstalk, the research interest is to realize a permutation that will use the minimum number of passes (to route the input request to output without crosstalk). This routing problem is an NP-hard problem. Many heuristic algorithms have been proposed and designed to perform the routing such as the sequential algorithm, the sequential down algorithm, the degree-ascending algorithm, the degree-descending algorithm, the Simulated Annealing algorithm and the Ant Colony algorithm. The Zero algorithms are the new algorithms that have been proposed in this thesis. In Zero algorithms, there are three types of algorithms namely; The Zero X, Zero Y and zeroXY algorithms. The experiments conducted have proven that the proposed algorithms are effective and efficient. They are based on routing algorithms to minimize the number of passes to route all the inputs to outputs without crosstalk. In addition, these algorithms when implemented with partial ZeroX and ZeroY algorithms would yield the same results as the other heuristic algorithms, but over performing them when the execution time is considered. Zero algorithms have been tested with many cases and the results are compared to the results of the other established algorithms. The performance analysis showed the advantages of the Zero algorithms over the other algorithms in terms of average number of passes and execution time.